Varied Teaching Methods Revolutionize English Speaking Skills Education: Metode Pengajaran yang Bervariasi Merevolusi Pendidikan Keterampilan Berbicara Bahasa Inggris - Fatmakiyyah, Fatmakiyyah; Santoso, Dian Rahma (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative study investigates the teaching methods used by English teachers in three Muhammadiyah Junior High Schools in Pasuruan Regency to enhance students' speaking skills. Interviews and observations were conducted with one English teacher from each school. Results reveal that teachers employ a variety of methods including Communicative Language Teaching, Discussion Method, and Total Physical Response, adapting them to address specific teaching challenges and student needs. The study suggests the importance of creating engaging learning environments and utilizing diverse teaching strategies to improve students' speaking abilities, offering valuable insights for English language educators to enhance their teaching practices. Hightligh: Diverse Methods: Communicative Language Teaching, Discussion Method, Total Physical Response. Student Adaptation: Methods tailored to student challenges and language learning needs. Engagement Vital: Engaging environments and varied strategies crucial for speaking improvement. Keywords: English language teaching, Muhammadiyah schools, speaking skills, teaching methods, qualitative research.